If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -13 = 6x + -4 Reorder the terms: -13 + 3x = 6x + -4 Reorder the terms: -13 + 3x = -4 + 6x Solving -13 + 3x = -4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -13 + 3x + -6x = -4 + 6x + -6x Combine like terms: 3x + -6x = -3x -13 + -3x = -4 + 6x + -6x Combine like terms: 6x + -6x = 0 -13 + -3x = -4 + 0 -13 + -3x = -4 Add '13' to each side of the equation. -13 + 13 + -3x = -4 + 13 Combine like terms: -13 + 13 = 0 0 + -3x = -4 + 13 -3x = -4 + 13 Combine like terms: -4 + 13 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| 4V=42-2V | | 2x+10=10x-4 | | -2y/2=8-3x/2 | | 2/3(9x-12)=24 | | 2L+2(10)=60 | | f(x-1)=4x^2+5x+7 | | X+3x-1=33 | | 16+7c=51 | | x^2+.12x-.054=0 | | 2w=2.56 | | -28+p=(p-10) | | -26/50 | | 22x-3.5=18.5 | | y+6(y-9)= | | y=41x-(88000+33x) | | 7x+6x+3+8=10x+5+2x | | 13x+.64x=100 | | 6x-14-4x=6x-9 | | (4X+7)+(2X-16)= | | 7(4y-9)-(2y+6)= | | 3y-10=x | | u=5(8n+35)+6(n+1) | | 5n+9=3n-1 | | (4c^8d^-6)/8d^3)^-1 | | (4X+7)+(2-16)= | | 5m=18+2m | | log(9x)=1 | | (2+y)(2y+3)=0 | | x=-14+3(4) | | (-4.5)+4.9+3.4= | | 18+10=m | | 2.5x-3(x+1)=12 |